The Effect of Earnings Management and Inventory Intensity on Tax Aggressiveness with Independent Commisioners as Moderating Variables - Sri Ayem; Putra Panjaitan (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to determine the effects of earnings management and inventory intensity on tax aggressiveness, with independent commissioners as a moderating variabel. Taxation issues arise due difference in tax perceptions between companies and the government, resulting in tax aggressiveness where companies consider taxes to be a burden and therefore attempt to develop both legal and illegal strategies to avoid taxes, while the government considers taxes to be state revenue. This research is a quantitative study focusing on manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2021-2024. The method used in this study is multiple linear regression analysis using SPSS software. The results show that earnings management and inventory intensity simultaneously have a positive effect on tax aggressiveness. In addition, independent commissioners can positively influence the effect of earnings management on tax aggressiveness and are unable to moderate the effect of inventory intensity on tax aggressiveness. this research uses the most recent data and adds a moderating variable, namely independent commissioners, which are expected to strengthen and weaken the influence of earnings management and inventory intensity on tax aggressiveness.